HUBUNGAN TEMPAT PENAMPUNGAN AIR, SISTEM PEMBUANGAN SAMPAH DAN KONDISI LINGKUNGAN RUMAH DENGAN KEBERADAAN JENTIK NYAMUK AEDES AEGYPTI - Reni Novitasari; Eko Heryanto (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
One of the diseases caused by poor environmental hygiene is Dengue Fever (DHF). Data from the OKU District Health Office, dengue cases in 2022 were 43 cases. Data from the UPTD Puskesmas Sekar Jaya showed that there were 6 cases of DHF in 2022. Of the 4 villages in the UPTD Puskesmas Sekar Jaya area, the highest number of DHF cases occurred in Sekar Jaya Village, with 3 cases. Some factors that influence the occurrence of DHF are the presence of Aedes aegypti larvae and behavioral factors of the host itself. The research design used Cross Sectional. The population was all heads of families totaling 2,373 heads of families with a sample size of 94 respondents. The statistical test used was the chi square test. Based on univariate analysis, it was known that 57 (60.6%) respondents did not have the presence of Aedes aegypti mosquito larvae, 55 (58.5%) respondents with good water reservoirs and 52 (55.3%) respondents with a good garbage disposal system. The results of bivariate analysis obtained the variable results of the presence of mosquito larvae with a p value of 0.027, water reservoirs with a p value of 0.000, and garbage disposal with a p value of 0.012. There is a significant relationship between the presence of mosquito larvae, water reservoirs and garbage disposal in Sekar Jaya Village, Sekar Jaya Health Center.